Extraction and characterization of a pectin from sea buckthorn peel - Zhu, Yulian; Liu, Keshan; Yuen, Michael; Yuen, Tina; Yuen, Hywel; Peng, Qiang (Frontiers in Nutrition, 2022)
Sea buckthorn peel is the by-product of the sea buckthorn processing, which contains many bioactive compounds. In this paper, sea buckthorn high methoxyl pectin (SBHMP) was obtained, with a yield of 8% and a light-colored. The SBHMP was a high methoxyl with a degree of esterification of 57.75% and uronic acid content of 65.35%. The structural and morphological characterization of SBHMP were analyzed by high-performance liquid chromatography, Fourier-transform infrared spectroscopy, and scanning electron microscopy. Results showed that SBHMP presented a sheet and layered stacked morphological, and was mainly composed of galacturonic acid, arabinose, galactose, rhamnose, and mannose, which indicated that SBHMP mainly consisted of homogalacturonan (HG) and rhamnogalacturonan-I (RG-I) type pectin polysaccharides. In addition, SBHMP also presented significant gel, thickening, and emulsifying properties. The results exhibited that SBHMP could form jelly-like gels under acid and high sucrose conditions, presenting a shear-thinning behavior and increasing apparent viscosity with the enhancement of pectin and sucrose contents. Besides, SBHMP could form oil-in-water emulsions with pectin concentrations of 1.0–3.0%. When the SBHMP concentrations were 2.0 and 3.0%, the emulsions were stable during 7 days of storage. Findings in this paper demonstrated the potential of SBHMP to be a food thickener and emulsifier and support the in-depth utilization of sea buckthorn by-products.